E-waste management: Are we ready for it? A study on the awareness of COIT students toward e-waste management - Chen L.F.; Yee H.W. (2023)
Electronic waste (e-waste) management is not new in Malaysia. It is always related to the recycle, reuse and reduce of e-waste and these may be the only approaches of managing e-waste today. Basically, there is no perfect solution in e-waste management. Recycle and reuse only temporary transfer the e-waste to other places and after sometimes, the e-waste still landed on the landfill. Reducing the use of toxic materials is a better way of managing e-waste, but for time being, it is difficult and not cost effective to replace and reduce all these materials. This paper carry out a survey onto the students from the College of Information Technology (COIT), UNITEN in order to identify whether the students are aware of the essentiality of e-waste management. Based on the study results, it shows that COIT students are not ready for e-waste management and the factor of not offering of Green IT or e-waste management subject is having the main factors of the unawareness of e-waste management. 2011 IEEE.